(untitled) (Medico Legal Update, 2021)
Workplace (occupational) injuries pose major public health and socioeconomic developmental issue leading to mental and physical disability. However, efforts towards investigation of determinants among factory workers are very minimal in developing countries. Thus, this study aimed at evaluation of the Socio demographic profile, identify determinants and pattern of occupational injury among victims of industrial accidents was undertaken. This retrospective study was conducted over a period of 2 years in a Tertiary care centre at Kancheepuram district. Total of 4693 work place accident cases visited the hospital (OP and IP) between January 2018 to December 2019. On statistical analysis, Male preponderance was noted and 3/4th of the study population belonged to age group of 20-40 years. Most of accidents 2815 (59.98%) took place in semi urban area and 1549 (33.01%) victims occurred in the Urban locality. 44.13% of the cases (2071) occurred in the summer season. 36% of the events were seen between 12 Noon to 6 PM. It was noted that abrasion was the commonest injury noted (69%, 3238) and the least common were burns injury (12%, 563). Upper limb injuries were noted in almost 3/4th of the cases (3426) and intracranial haemorrhages were observed in 55 cases. Only 1/3rd of the cases used protective gear during the incident. Lack of effective training, sleeping disturbance, and job stress increased the risk of occupational injury. Hence, providing health and safety education with importance given to the younger male workers, reducing stressors, and offering sleep health education were recommended.